In vitro and in vivo evaluation of certain chemicals against Beauveria bassiana-pathogen of white muscardine disease of Silkworm, Bombyx mori L. - Ghosh, Lipika; Neela, FA; Alam, MS; Pasha, MK (University Journal of Zoology, Rajshahi University, 2007)
Key words: Chemicals; white muscardine disease; Beauveria bassiana, Bombyx mori L. Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 27-32